Impact of Augmented Reality E-Flashcards with the Team Games Tournament Cooperative Learning Model on Biology Learning Outcomes of High School Students - Brylliant, Mustika Ayu; Nurcahyanto, Guntur (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
The use of technology in science education facilitates students' understanding of abstract material such as the human digestive system. This study investigates the effect of integrating Augmented Reality (AR)-based e-flashcards into the Team Games Tournament (TGT) model on students' biology learning outcomes. The research employed a one-group pretest-posttest pre-experimental design, involving 33 eleventh-grade students at SMAIT Al Hikmah Boyolali, Central Java, conducted over one week in March 2025. A 15-item multiple-choice test based on Bloom's taxonomy (C4–C5) was used to measure learning outcomes. The instrument was validated by expert judgment and item analysis. Findings showed an increase in the average posttest score (76.38 ± 6.50) compared to the pretest (35.59 ± 11.67). The Wilcoxon signed-rank test revealed a significant difference (p < 0.001), with a large effect size (r = 0.78), indicating the effectiveness of the intervention. The results suggest that AR-based e-flashcards, when combined with the TGT model, enhance student engagement, collaboration, and understanding of abstract concepts. This approach offers a promising strategy for improving learning outcomes in high school biology instruction.